Langerhans cell histiocytosis in a young patient with Pitt–Hopkins syndrome. Issue 11 (18th September 2020) - Macchiaiolo, Marina; Panfili, Filippo Maria; Gonfiantini, Michaela Veronika; Mastrogiorgio, Gerarda; Buonuomo, Paola Sabrina; Gaspari, Stefania; Longo, Daniela; Zollino, Marcella; Bartuli, Andrea
Abstract: Pitt–Hopkins syndrome (PTHS, MIM #610954) is a rare neurodevelopmental disease characterized by the association of intellectual disability, characteristic facial gestalt and episodes of abnormal and irregular breathing. PTHS is due to heterozygous loss‐of‐function variants in the TCF4 gene (transcription factor 4, MIM #602272) encoding for a basic helix–loop–helix transcription factor. TCF4 is highly expressed during early development of the nervous system, and it is involved in cellular differentiation and proliferation. Since the first clinical description in 1978, less than 200 PTHS patients have been described. A comprehensive phenotype, especially regarding cancer predisposition, is not yet well defined. We report the case of a 7‐year‐old boy affected by PTHS with a 4‐week history of progressive swelling of the frontal bones diagnosed with Langerhans cell histiocytosis.